Alternative integrated pest management methods for controlling Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae) - Manu, Naomi (Kansas State University, 2023)
Tyrophagus putrescentiae (Schrank) (Acaridae), commonly known as the mold mite, cheese mite and ham mite, is one of the most important pests of dry-cured hams. Methyl bromide is the most effective fumigant that has been used to control ham mites. Methyl bromide is now banned for most food uses and is being phased out of use in many countries in accord with the Montreal Protocol on substances that deplete the ozone layer of the earth’s atmosphere. This work is part of a long-term effort to find alternatives to methyl bromide for use in controlling ham mites. In an integrated pest management program, different tools play a role in the successful control of insect pests. Hence, effective, feasible and economically friendly integrated pest management (IPM) tools are needed to help in the control of these ham mites in the dry-cured ham industry. Work for this dissertation is divided into four independent sections by chapter, as described below. Plant essential oils and food-safe compounds were evaluated as repellents for their effectiveness at controlling mites. Experiments to assess the repellency to orientation, oviposition, and population growth of mites on 5 mm³ and 25 mm³ pieces of aged country hams were conducted. Test compounds at different concentrations were dissolved in required solvents and compared to the solvent control. Results indicated that nootkatone and a blend of C8, C9 and C10 straight-chain hydrocarbons had repellency indices of (RI) of 85.6% and 82.3%. Geraniol had the highest RI of 96.3% at 0.04 mg/cm². Ham pieces dipped in C8910 and nootkatone at 150 ppm each had RIs of 89.3% and 82.8%, respectively. In general, as the concentrations of test compounds increased, the numbers of eggs that were laid on these treated ham cubes decreased after the 48h exposure time. In the second study, about fifteen commercially available acaricides were screened as surface applications, and four chemicals were effective against mites. The persistence of these four chemicals over time was further assessed over eight-week periods by applying the recommended rate to three different surfaces: metal, concrete and wood. Results indicated that acequinocyl and amitraz were very persistent and effective at killing mites throughout the experiment period even after the sixth to eighth week aging of the sprayed surfaces, hence suggesting good efficacy for commercial use. Traditionally, the use of residual pesticides and fumigants have been the primary way to control stored product pests, including ham mites. Since the use of these products are being minimized to embrace more environmentally friendly and humanly safe alternatives, the objective of this third experiment was to evaluate different physical barriers to exclude ham mites in a simulated ham-aging facility. The physical treatments included both liquid and sticky barriers. The liquid treatments were water, soapy water, vegetable oil and mineral oil whereas the dry sticky treatment were petroleum jelly and a sticky coating used in insect traps. These experiments indicated that physical barrier treatments can significantly reduce the number of ham mites that may walk up from the floor to infest dry cured hams while they were hanging on racks above the floor. However, barrier methods used for exclusion alone cannot eradicate ham mites in an aging room. Hence, it can certainly be used in conjunction with other pest management tools for successful protection of dry-cured hams.
Keywords: Management; Dry-cured ham; Storage mites; Physical barriers; Stored products; Repellency